2013
DOI: 10.1080/10496505.2013.774277
|View full text |Cite
|
Sign up to set email alerts
|

A Framing Analysis of Newspaper Coverage of Genetically Modified Crops in Kenya

Abstract: There was much public debate in Kenya about genetically modified (GM) crops when the national Biosafety Bill went through the parliamentary process toward enactment into law. This study analyzed how GM crops were framed in three mainstream Kenyan newspapers-the Daily Nation, The Standard, and Taifa Leo-during the period. The agriculture frame was predominant in the Daily Nation and The Standard, while the safety and regulation frames dominated coverage in Taifa Leo. Only 34.7% of articles were neutral in tone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Although this frame was found in other studies, in this sample it was incorporated much more frequently (Abbot et al, 2001;Lore et al, 2013). This finding was interesting because this frame focused more on ethical and moral standards, such as business transparency and honesty, rather than the negative or positive effects of labeling genetically modified organisms.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 46%
See 1 more Smart Citation
“…Although this frame was found in other studies, in this sample it was incorporated much more frequently (Abbot et al, 2001;Lore et al, 2013). This finding was interesting because this frame focused more on ethical and moral standards, such as business transparency and honesty, rather than the negative or positive effects of labeling genetically modified organisms.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 46%
“…After conducting a pilot test, the researchers noticed its frequency in the sample and included it for the final coding procedure. Although earlier studies identified many frames used by newspapers and mass media outlets to convey GMO issues (Abbot et al, 2001;Lore et al, 2013), they did not recognize the right to know frame. However, in this sample it was the most prominent (n = 97, 59.9%).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 96%
“…First, by comparing the number of times that news articles discussing biotechnology mention risks, benefits, and terms relating to them, and by comparing the coverage of biotechnology in Kenya to an international sample of newspapers, we find that the media in Kenya generally do not provide a balanced reporting of risks and benefits relative to the international newspapers in our study. Like Lore et al (2013), we find that there is variation among Kenyan newspapers in their reporting of perceived risks and benefits. However, we find that more news articles contain references to benefits than to risks of GMOs.…”
Section: Commentarymentioning
confidence: 79%
“…For example, Lore et al (2013) identified articles searching for specific words related to risks and benefits, such as "genetically modified food is harmful …" (p. 141). However, unlike Lore et al (2013), who coded these attribute words for positive, negative, or neutral tone, we seek only to identify the attributes.…”
Section: Media and Public Opinionmentioning
confidence: 99%
See 1 more Smart Citation